Determinación de la satisfacción de los servicios turísticos de las empresas de transporte terrestre de la ciudad de Yurimaguas a Tarapoto - Collazos Riva, Ruth Milagros (2023)
The thesis, "Determination of the satisfaction of the tourist services of the land transport companies from the city of Yurimaguas to Tarapoto", had the purpose of studying the valuation of the tourist services companies by the visitors who travel on the route from Yurimaguas to Tarapoto or vice versa. The methodology used was from a quantitative approach, descriptive design, the population as the sample was 44 tourists from the 11 tourist transport companies that exist in the city of Yurimaguas, the instrument was applied to 4 visitors or tourists by transport company. The survey comprises questions with general data with 4 questions and the questionnaire has 20 questions. It has been shown that the survey has a high reliability of 0.926 measurement according to the Cronbach's Alpha indicator, this means that the data collection instrument measures what it wants to measure. It was possible to demonstrate the hypothesis where it was rejected because it is not significant that "the tourist services provided by land transport companies from Yurimaguas to Tarapoto do not significantly satisfy tourists or visitors."